PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS PENDEKATAN SAINTIFIK PADA MATERI TRIGONOMETRI KELAS X SMA - Uri Putri Riani (Jurnal Edukasi dan Penelitian Matematika, 2021)
This research aims to develop interactive learning multimedia based on scientific approach in trigonometric material of class X SMA which is valid and practical. This type of research is a design research type of development studies with the Plomp development model which consist of preliminary research phase and prototyping phase. The preliminary research phase includes need analysis, student analysis, curriculum analysis and concept analysis. Prototyping phase was the stage of design interactive learning multimedia consisting of prototype 1, prototype 2, prototype 3 and prototype 4 which were evaluated using a formative evaluation design. Based on the validation result, the interactive learning multimedia is considered valid with a validity level of 88,57%. The practicality level by students was 87,73%  and hhe practicality level by teacher was 89,58%  .Keywords ‒ Interactive learning multimedia, scientific approach, valid, practical.